Hydrogen Storage Solutions in the Power-to-X Framework - Markovic,Petra (2025)
Power-to-X (PtX) is an emerging approach in decarbonizing industries hard to electrify, and is in many cases requiring stable hydrogen supply to maximize production. Hydrogen is produced via electrolysis and requires large amounts of electricity, which can be expensive, especially when considering highly fluctuating electricity prices. One solution in reducing electricity related costs is to integrate a hydrogen storage in the PtX system, acting like a buffer of hydrogen. The idea is to produce hydrogen when electricity prices are low and when prices are high, hydrogen from the storage would be used in the process, ensuring stable hydrogen supply. This thesis evaluates a range of hydrogen storage solutions, examining their advantages, disadvantages, capacity, technological readiness levels (TRLs), and overall suitability for different applications. Pressure storage tanks are fully mature and flexible at moderate levelized cost of storage (LCOS) but face challenges with space efficiency, scalability, and safety, limiting their use to small or medium scales. Underground storage options, like salt caverns and lined rock caverns, are well-suited for large-scale PtX applications, offering low LCOS and safety benefits but depend on geological conditions. Emerging technologies such as lined rock holes show promise for moderate LCOS and enhanced space efficiency. Liquefied hydrogen storage is mature and compact but energy-intensive and costly due to the liquefaction process. Chemical storage methods, including LOHCs and metal hydrides, provide space-efficient and stable storage but are constrained by high energy requirements for hydrogenation and dehydrogenation. Metal hydrides offer the highest storage density but also the highest energy consumption. The LCOS analysis shows consistent trends, with salt caverns as the most cost-effective for large-scale storage, while LOHCs and liquid hydrogen are less economical. Excluding electricity costs barely affect the relative LCOS of the technologies, but does have a meaningful impact on the energy intensive storage alternatives (liquid hydrogen storage and material-based storage). The thesis concludes that no single solution fully addresses the challenges of hydrogen storage, and the optimal choice depends on application-specific requirements such as cycling frequency, storage capacity, cost, and scalability. Recommendations for suitable PtX applications are summarized in a qualitative evaluation, emphasizing the importance of flexible and efficient storage solutions for hydrogen in PtX systems.
Keywords: Hydrogen Storage; Levelized Cost of Hydrogen Storage